Restoring The Rights Of Child Victims Of Sexual Crimes In Indonesia Throughs Victim Impact Statement - Silitonga, Tumpal Paskalis (Universitas Negeri Semarang, 2025)
The position of victims in the Indonesian Criminal Justice System currently seems to have been